Differential Effect of Intrauterine Growth Restriction on Childhood Neurodevelopment: A Systematic Review. Issue 2 (June 2016) - Murray, E.; Fernandes, M.; Fazel, M.; Kennedy, S.H.; Villar, J.; Stein, A.
Abstract : ( BJOG . 2015;122(8):1062–1072) Intrauterine growth restriction (IUGR) is the second leading cause of perinatal morbidity and mortality worldwide, and is associated with significant neurodevelopmental impairment. Despite this, there have been no systematic reviews that examine the effects of IUGR on various neurodevelopmental domains throughout childhood (up to 12 y), nor has there been an attempt to differentiate the contributions of several insults often are associated with IUGR to childhood neurodevelopmental outcomes.